Editorial - Silva, Fabián Leonardo Benavides (Universidad Santo Tomás, Bogotá, Colombia, 2011)
The magazine Análisis with this issue on ways of making history, intends to add and contribute in diferent forms to a debate of great academic importance, which not only concerns the ields of history or human sciences, but also concerns all exact sciences. The common debate in all the branches of human knowledge is about wondering at the time of formulating a research problem: On which topic is it necessary to inquire or write about? and from what theoretical or methodological point(s) of view is this best done. There are often attempts to answer both questions, on the one hand using the postulates by those authors regarded as “foundational” in a speciic science or knowledge, on the other hand, taking into account the issues of greater repercussions in the academy. This leads us to think that everything goes and consequently, it is possible to appeal to interdisciplinary, transdisciplinary, counterdisciplinary, multimethodological or multiparadigmatic approaches. It is however clear that there are no concrete formulas to deal with and develop a speciic research problem and that the whole theoretical-methodological corpus used is valid as for as it demonstrates its relevance and efectiveness to solve the problem. In the rigor with which the researcher chooses his “tools” and the level of relexivity that he uses in their validity process, he greatly reduces the risk of the research project becoming a collage or a string of snippets.